Gray mold rot of tomato and bell pepper under protected cultivation in Himachal Pradesh - NARENDER K. BHARAT, MEENU GUPTA* and (Indian Phytopathology, 2013)
Himachal Pradesh is an emerging producer of greenhouse grown vegetables especially tomato and bell pepper. These crops are grown throughout the year under protected cultivation conditions and fruits are transported to the northern plains which fetch good remuneration to the growers of this hilly state. Greenhouses vary in structural complexity from simple plastic film covered tunnels with no assisted ventilation or naturally ventilated to tall multi span glass to plastic covered structures covering several hectares and having sophisticated computer controlled environments. Climate inside the naturally ventilated greenhouses is generally warm and humid, which is ideal for raising crops but at the same time provide congenial conditions for development of many pathogens (7, 8). The dense plant population under greenhouse creates high relative humidity, with shaded regions in the canopy that are moist and dark. Training, pruning and fruit picking cause both large and microscopic wounds. The damaged leaves and stems are prone to infection of many kinds of pathogens. Therefore, due to the prevalence of such congenial conditions in greenhouses, these crops are severely infected with leaf spotting and fruit rotting fungi.